2017
DOI: 10.2147/ott.s143491
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous sheath interacting protein 1 overexpression is associated with unfavorable prognosis in bladder cancer: a potential therapeutic target

Abstract: The study aimed to investigate the clinical significance of fibrous sheath interacting protein 1 (FSIP1) in bladder cancer, and its potential relevance to the survival of patients with bladder cancer. A total of 225 surgical excised-bladder cancer tissues were collected from the patients with the follow-up data >5 years. The FSIP1 expressions were assayed using immunohistochemistry. The messenger RNA (mRNA) and/or protein levels of FSIP1 in fresh bladder tumor tissues as well as bladder cancer cell lines were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
(22 reference statements)
0
12
0
Order By: Relevance
“… 19 , 25 Moreover, FSIP1 overexpression was found to induce cancer cell mitotic errors. 25 Indeed, previous studies have shown that FSIP1 was overexpressed in non-small-cell lung carcinoma, 23 breast cancer, 21 and bladder cancer 30 and its overexpression was associated with poor survival in patients carrying these tumors. Thus, FSIP1 is considered to be an oncogene in these cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 25 Moreover, FSIP1 overexpression was found to induce cancer cell mitotic errors. 25 Indeed, previous studies have shown that FSIP1 was overexpressed in non-small-cell lung carcinoma, 23 breast cancer, 21 and bladder cancer 30 and its overexpression was associated with poor survival in patients carrying these tumors. Thus, FSIP1 is considered to be an oncogene in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 27 29 Our published data revealed that FSIP1 protein was significantly upregulated in bladder cancer tissues, and it was associated with unfavorable clinicopathological features as well as poor survival of bladder cancer patients. 30 Thus, further investigation of FSIP1 involvement in bladder cancer could provide a novel insightful information for the role of FSIP1 in the regulation of bladder cancer biological behavior, such as tumorigenesis, progression, and therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, considerable attention has been deserved to explore novel therapeutic targets of luminal breast cancer . Previous investigations have reported that overexpression of FSIP1 predicted unfavorable prognosis in NSCLC, bladder cancer, and breast cancer . There also is evidence to support that FSIP1 can serve as a potential target for steroid receptor coactivator‐3 in breast cancer, a gene involved in cancer progression and poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…Fibrous sheath interacting protein 1 (FSIP1) is a cancer/testis antigen (16) expressed in the majority of breast cancers, bladder cancers, and nonsmall cell lung cancer (17)(18)(19). Our previous findings and those of others show that high FSIP1 expression is associated with increased invasiveness and poor prognosis in breast cancer (19,20).…”
mentioning
confidence: 82%